A randomized clinical trial of glenohumeral joint steroid injection versus suprascapular nerve block in patients with frozen shoulder: a protocol for the Therapeutic Injections For Frozen Shoulder (TIFFS) study. (16th March 2023) - Jump, Christopher M.; Mati, Wael; Maley, Alex; Taylor, Rebecca; Gratrix, Karen; Blundell, Clare; Lane, Suzanne; Solanki, Nilesh; Khan, Maqsood; Choudhry, Muhammad; Shetty, Vishwanath; Malik, Rayaz A.; et al.
Abstract : Aims: Frozen shoulder is a common, painful condition that results in impairment of function. Corticosteroid injections are commonly used for frozen shoulder and can be given as glenohumeral joint (GHJ) injection or suprascapular nerve block (SSNB). Both injection types have been shown to significantly improve shoulder pain and range of motion. It is not currently known which is superior in terms of relieving patients' symptoms. This is the protocol for a randomized clinical trial to investigate the clinical effectiveness of corticosteroid injection given as either a GHJ injection or SSNB. Methods: The Therapeutic Injections For Frozen Shoulder (TIFFS) study is a single centre, parallel, two-arm, randomized clinical trial. Participants will be allocated on a 1:1 basis to either a GHJ corticosteroid injection or SSNB. Participants in both trial arms will then receive physiotherapy as normal for frozen shoulder. The primary analysis will compare the Oxford Shoulder Score (OSS) at three months after injection. Secondary outcomes include OSS at six and 12 months, range of shoulder movement at three months, and Numeric Pain Rating Scale, abbreviated Disabilities of Arm, Shoulder and Hand score, and EuroQol five-level five-dimension health index at three months, six months, and one year after injection. A minimum of 40 patients will be recruited to obtain 80% power to detect a minimally important difference of ten points on the OSS between the groups at three months after injection. The study is registered under ClinicalTrials.gov with the identifier NCT04965376. Conclusion: The results of this trial will demonstrate if there is a difference in shoulder pain and function after GHJ injection or SSNB in patients with frozen shoulder. This will help provide effective treatment to patients with frozen shoulder. Cite this article: Bone Jt Open 2023;4(3):205–209.